Community Service: The Transformation of Badminton Learning Through Virtual Reality Technology in Elementary Schools - Novri Gazali; Dea Mustika; Romi Cendra; Ahmad Rahmadani; Rapindo; Sukaredo (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2025)
The community service activity aims to introduce 3D Virtual Reality technology as an innovation in badminton learning at SD Negeri 168 Pekanbaru. The activity stages in the implementation of this PkM program consist of several main stages, namely preparation, implementation, evaluation, and evaluation of the implementation and sustainability of the program. The results of this activity confirm that learning using 3D virtual reality technology has a significant positive impact on improving students' knowledge, skills, and attitudes. The technology proved effective not only in improving theoretical understanding but also in developing practical skills and building higher motivation. This community service activity has successfully achieved the main objective, which is to increase students' interest and involvement in badminton through the use of 3D Virtual Reality (VR) technology. The evaluation results showed a significant increase in the aspects of cognitive knowledge, psychomotor skills, and affective attitudes of students after participating in this technology-based learning. Nevertheless, the success of this program is also accompanied by challenges, especially the need for teacher training in the use of VR technology to ensure the sustainability of the program in the future